Determinants of Diarrhea Incidence in Toddlers in the Work AreaPaal V Health Center 2024 - Widya Dina Fitri; Adelina Fitri; Andree Aulia Rahmat; Helmi Suryani Nasution; Kasyani Kasyani (Lembaga Pengembangan Kinerja Dosen, 2025)
Background: Diarrhea is a condition in which a person experiences bowel movements more than three times a day with liquid-textured feces, often accompanied by mucus or blood, and occurs more often than usual. The purpose of this study was to determine the determinants of diarrhea in toddlers in the work area of ​​the Paal V Health Center in 2024. This study is a quantitative study using a Cross Sectional approach method. The sample in this study was 167 mothers of toddlers with a purposive sampling technique. The study was conducted from August 2024 to January 2025. The research instrument used a questionnaire and observation sheet. The variables used were CTPS habits, exclusive breastfeeding, visits to integrated health posts, maternal employment status, clean water sources, healthy toilets. Cronbach's results Validity Test Diarrhea incidence (0.404), CTPS habits (0.632), exclusive breastfeeding (0.636), visits to integrated health posts (0.690). The results of the CTPS habit analysis obtained p-value (0.034), exclusive breastfeeding (0.016), visits to integrated health posts (0.107), maternal employment status (0.042), clean water sources (0.154), healthy toilets (1.000). There is a relationship between CTPS habits, exclusive breastfeeding, maternal employment with the incidence of diarrhea in toddlers. There is no relationship between visits to integrated health posts, clean water sources, healthy toilets with the incidence of diarrhea.